(3Gdbhd GdCSO aj Mce fUjH GdejJ aj Gdhba ef ZjQ hdOs - (3eMeO Hf HjQe GdKGfjs
(3ChdgG (B:s
(3HYO JUOjQ GdebGd HMeO Pi GdLdGd agPg QSGdI LejdI GdhVY LdjdI GdfaY ehSheI HGdbhd ai Mce fUjH GdejJ ai Gdhba s
(3BNQgG (B:s
(3hEf CQGO OGNdg adG CYde NdGakG ai Pdc hGddg JYGdi CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs